The Effect of the Increase in Population on the Unemployment Rate in Central Sulawesi Province Period 2018-2020 - Salsabila, Alya; Azaria, Naura Sultania; Desmawan, Deris (Journal Of Accounting Management Business And International Research, 2022)
The manufacture of the journal is intended to meet one of the task of economic development courses with the lecturer Deris Desmawan, SE, M.Si. This study attempts to test the relationship between increase in the number of people with unemployment in central sulawesi province 2018-2020 a period of years. This research using secondary data, data sourced from BPS (Badan Pusat Statistik) , and research before discuss on a subject of same. In this research using two variables in this research of improved the population and unemployment, Technique the analysis used is using the regression equation is and the descriptive statistics. Research findings show that the variable an increase in the population of the against the number of unemployment have ties a correlation in which very strong and in line. The results can be seen from significance and testing shows the testing of hypotheses satisfactory results positive and significant